Al borde del universo hueco Salvador Elizondo: "En la playa" - Révész, Enkratisz (Verbum – Analecta Neolatina, 2010)
The aim of this paper is to reveal — through the analysis of one of the early short stories of Salvador Elizondo, "En la playa" — some of the most important features that already present in these early works of the Mexican writer and which recur obsessively later, displaying an unusual, rather idiosyncratic and dark universe. We argue that due to their outstanding literary value, the works of the writer should deserve wider appreciation. Also, with the help of this particular work, we would like to call attention to the early short stories of Elizondo, which, we think, have not received enough critical attention in the shadow of the author's two novels, as well as later texts focusing on the problem areas of the writing process.